Connecting - Helen Walker; Steven DeGeorge; Johanna Rodgers; Jeremiah Conway (Journal of the Assembly for Expanded Perspectives on Learning, 2007)
Helen Walker. Connecting. Steven DeGeorge —The Things They Bring to School . Johanna Rodgers —Translating Authority Jeremiah Conway —Emily's Cave